(untitled) (Research, Society and Development, 2021)
The study aimed to gather information about the socioeconomic aspects based on the reports from Spix and Martius expedition compared to the present day. The studied region is inserted in the basin of the Canindé River, of the semi-arid region of Piauí. The research was based on the report of Spix and Martius’s book Viagem pelo Brasil, government websites, province reports and bibliographic research. The main changes that took place in the region were the move of the Capital from Oeiras to Teresina, the use of the navigability of the Parnaíba River and the construction of the Dairy Factory in Campinas, which started wage employment in Piauí. In 1819, the region was sparsely populated (71,370 inhabitants), with low demographic density (- 0.28 inhabitants / km2), there were only the county of Oeiras and some towns. After 200 years, the population reached 3,118,360 with a demographic density of 12.4 inhabitants / km2, which is still considered low. Piauí is currently divided into 224 counties, 16 of which make up the study region, of which Oeiras and Paulistana have the largest population. The entire population today has access to education and the counties with the highest Basic Education Development Index (IDEB) are Oeiras and Acauã. The region is grouped into development territories and its main economic potentials are agribusiness, apiculture, livestock farming, cashew farming, sheep farming and wind power. Even in the face of advances and development, socioeconomic indicators show that the semi-arid region remains underdeveloped, with the need to expand public policies and private sector interventions, identifying the potential of counties, from a regional development perspective.